Evidence‐based insomnia treatment strategy using novel orexin antagonists: A review - Taro Kishi; Maika Nishida; Michinori Koebis; Takehiro Taninaga; Kenzo Muramoto; Naoki Kubota; Margaret Moline; Kenji Sakuma; Makoto Okuya; Ikuo Nomura; Nakao Iwata (Wiley, 2021)
Abstract Most conventional insomnia medications are gamma‐aminobutylic acid receptor agonists. However, physical dependence is a concern and one of the major limiting factors for long‐term treatment. The dual orexin receptor antagonists, suvorexant and lemborexant, were recently approved for treating chronic insomnia, giving a novel pharmacotherapeutic option. Because there are no comparative studies on these drugs, a network meta‐analysis was conducted, which is suitable for comparing interventions. According to this analysis, 5‐ and 10‐mg lemborexant were superior to 20‐mg suvorexant because of the greater improvement in initiating sleep after 1‐week administration. Furthermore, 5‐mg lemborexant (not 10 mg) and suvorexant were similarly well tolerated, without requiring discontinuation due to adverse events. We also overviewed the pharmacological and pharmacokinetic properties of lemborexant and suvorexant that may support these clinical outcomes. When compared to suvorexant, lemborexant quickly binds to the orexin receptors. The time to reach the maximum concentration after multiple administrations is shorter for lemborexant than for suvorexant. Considering these results, we recommend 5‐mg lemborexant as an initial treatment for insomnia, followed by 10‐mg lemborexant or suvorexant.